Pengaruh Physical Work Environment, Non-physical Work Environment, Person Job Fit, dan Person Organizational Fit terhadap Employee Performance: Inggris - Pamungkas, Purnomo Aji; Kurniawan, Ignatius Soni; Lysander, Muhammad Ahyar Syafwan (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
This study aims to determine the effect of physical work environment, non-physical work environment, person job fit, and person organizational fit on employee performance at Perumda Air Minum Tirta Merapi Klaten Regency. This research is a quantitative study with a sampling method using probability sampling technique, which means that each member of the population has the same opportunity to be selected as a sample. Respondents in this study were 109 employees of Perumda Air Minum Tirta Merapi Klaten Regency. The data analysis technique used is the validity test method, reliability test, correlation coefficient, coefficient of determination, multiple linear analysis, and hypothesis testing (partial t test and simultaneous F test) using SPSS 26.00 software. The results showed that the physical work environment did not have an effect on employee performance, the non-physical work environment did not have an effect on employee performance, Person Job Fit had a significant effect on employee performance, Person Organizational Fit had no effect on employee performance. The results of hypothesis testing obtained a regression R-Square value of 0.135 which indicates that 13.5% of the four independent variables affect employee performance while 86.5% is influenced by other variables.